Penentuan Massa dan Waktu Kontak Optimum Adsorpsi Karbon Aktif Dari Ampas Tebu sebagai Adsorben Logam Berat Pb - Riki Irwandi; Silvia Reni Yenti; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bagasse is one of the agricultural or industrial waste that can pollute the environment. One effort to improve the economic value of the bagasse can be done with the process into activated carbon. This study aimed to examine the mass effect of activated carbone and the time contact of the bagasse activated carbon adsorption used for heavy metal Pb adsorbent, and to study the characteristics of the activated carbon produced, among others, ash content and moisture content. This research was conducted in three phases were the raw material preparation, the manufacture of activated carbon, and the adsorption of Pb in PbSO4 solution. Variations in the mass carbone used in this study were 1; 2; and 3 gram. As for the time variation adsorption used were 30; 60; 90; and 120 minutes. Percent adsorption is best obtained when the mass of activated carbone of 3 grams and the optimum time contact of 90 minutes is equal to 94,15 %.Keywords: adsorbent, bagasse, activated carbone, mass of activated carbone, adsorption time